Kinematics analysis on accelerated motion using tracker video analysis for educational purposes - Renika, Jelita; Prima, Eka Cahya; Amprasto, Amprasto (Universitas PGRI Kanjuruhan Malang, 2024)
This study aims to determine the effectiveness of video analysis tracker-based practicum on the material of the motion of objects on an inclined plane and the motion of objects in free fall. The use of video tracker analysis-based practicum is useful for determining some kinematics parameters of objects that cannot only be calculated by traditional practicum methods. By using the video tracker analysis method, all object kinematics parameters can be found directly in visual form. The results show that (1) There is no relationship between mass and kinematics parameters. (2) There is an influence due to air friction on the acceleration value of the object. (3) The suitability of the concept with the tracker application produced with the error value in the experiment of object motion on an inclined plane () (4) The suitability of the concept with the tracker application produced with the error value in the experiment of object motion in free fall () Â (5) The graphical representation of the tracker is in accordance with the theory studied. This research implies that the existence of learning using practicum, especially practicum-based video tracker analysis can improve understanding and process skills in understanding science concepts. This research is written so that the programme can be further applied to science education.